PEGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN SUB SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2019 - Hasugian Raifian; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Intellectual Capital on Firm Value with Financial Performance as a mediating variable. The independent variable in this study is Intellectual Capital which is proxied by Value Added Intellectual Coefficient (VAIC). The dependent variable is the Value of the Company which is proxied by Price Book Value (PBV). And the mediating variable in this study is financial performance as proxied by Return On Assets (ROA). The population in this study is all of the various industries subsector companies that were officially listed on the Indonesia Stock Exchange for the 2015-2019 period as many as 38 companies. The sampling technique was carried out using purposive sampling method obtained by 34 companies. The analytical method used is path analysis. The results show that Intellectual Capital has a significant positive effect on Financial Performance, Intellectual Capital does not have a significant positive effect on Firm Value, Financial Performance has a significant positive effect on Firm Value, and Intellectual Capital has a positive influence on Firm Value with Financial Performance as a Mediation Variable.Keywords: Intellectual Capital, Financial Performance, Firm Value